2011
DOI: 10.1007/s11708-010-0137-3
|View full text |Cite
|
Sign up to set email alerts
|

New developments in mobile air conditioning systems in China

Abstract: Global warming poses serious global concerns, and the mobile air conditioning (MAC) industry must be promoted to reduce greenhouse gas emissions. In this paper, the development of the MAC system and components for new energy vehicles, low global warming potential (GWP) refrigerants, methods to control refrigerant leakage, and new energy-saving technologies in China are introduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…R1234yf has excellent environmental characteristics, which can be seen in Table 1 [2]. Chen et al [3] showed that it has similar performance characteristics to R134a by evaluating the current state in China. Some experimental studies compared using these two refrigerants in mobile air conditioners.…”
Section: Introductionmentioning
confidence: 99%
“…R1234yf has excellent environmental characteristics, which can be seen in Table 1 [2]. Chen et al [3] showed that it has similar performance characteristics to R134a by evaluating the current state in China. Some experimental studies compared using these two refrigerants in mobile air conditioners.…”
Section: Introductionmentioning
confidence: 99%
“…Farrington and Rugh [9] showed that an increase of the accessory load from 500 W to 3500 W will cause an EV range to decrease by 7 to 38%. Chen et al [10] noticed that total millage of an EV is decreased up to 50% when AC is on, making the vehicle not feasible for long journey transportation. Figure 1 shows the effect of HVAC system to the cruising range of the EVs.…”
Section: Introductionmentioning
confidence: 99%
“…According to Kwon et al (2012a), the EV driving range is approximately 140-160 km on a single charge; however, if the HVAC is turned on, this range is reduced by 20 to 30 %. Chen et al (2011) observed that the total mileage of an EV decreases by 50 % when the A/C is on, making the vehicle impractical for city transportation. AAC cooling loads are the most significant auxiliary loads (Zhang et al 2009;Kaushik et al 2011), so the AAC system has to consume energy efficiently to minimize the reduction in the cruising range when the AAC system is turned on.…”
Section: Introductionmentioning
confidence: 99%